EMERGING QUALITY CONTROL PERSPECTIVES FOR AYURVEDIC DRUG (AYUSHDHARA, 2017)
Ayush system of medicines based Herbal Pharmaceutical industry (ASU & H drug mfg) is having great potential and opportunities in India for development in future because of global acceptability of the medicinal plants & their value added products in Domestic & International Market as Ayurvedic, Unani and Siddha medicines, Herbal Nutraceuticals, Herbal Cosmoceutical, Herbal Health drinks, Dietary Health Supplements, Medicinal Plants / Crude Drugs, Herbal Extracts / Concentrates, Veterinary Medicines, Health Foods. India is rich with 771468 registered Ayush practitioners, 8667 licensed Ayurvedic drug manufacturing units. Quality Control/Assurance is the department, which controls all activities at various level of manufacturing as National & International standard. Ministry of Ayush continues to lay emphasis on up gradation of AYUSH educational standards, Quality control and standardisation of drugs, improving the availability of medicinal plant material, research and development and awareness generation about the efficacy of the system domestically and internationally. There are various issues & challenges related to drug quality for ASU&H Pharmaceutical Industries in India. It needs proper attention of policy makers and regulator & academia. Complete Implementation of GMP (schedule T) norm/guidelines and quality control/assurance procedure and activities is a big challenge for ensuring quality of drug.